Tillandsia borealis (Bromeliaceae), una nueva especie del norte de Mexico - Lopez Ferrari, A.R.=700 1 Espejo Serna, A.
(Es, En)
Ilus., 22 ref
Keywords: TAXONOMIA; BROMELIACEAE; ORGANISMOS INDIGENOS; DISTRIBUCION GEOGRAFICA; ECOLOGIA; MEXICO; TILLANDSIA BOREALIS